Structural elucidation and antidiabetic activity of fucosylated chondroitin sulfate from sea cucumber Stichopus japonicas. (15th June 2021) - Gong, Pi-Xian; Li, Qin-Ying; Wu, Yan-Chao; Lu, Wen-Yu; Zeng, Jun; Li, Hui-Jing
Graphical abstract: Highlights: A fucosylated chondroitin sulfate was isolated from Stichopus japonicus (FCS sj ). The precise structure of FCS sj was investigated by NMR spectra and HILIC-FTMS. Di-fucosyl branches attached to O-3 GlcA were found in FCS sj . FCS sj could improve the glucose uptake and glycogen synthesis in IR-Hep G2 cells. Abstract: A fucosylated chondroitin sulfate was isolated from the body wall of sea cucumber Stichopus japonicus (FCS sj ), whose structure was characterized by NMR spectroscopy and HILIC-FTMS. At the ratio of 1.00:0.26:0.65, three fucosyl residues were found: 2, 4-disulfated-fucose (Fuc2, 4S), 4-sulfated-fucose (Fuc4S) and 3, 4-disulfated-fucose (Fuc3, 4S), which were only linked to the O-3 of glucuronic acid residues (GlcA). Besides mono-fucosyl moieties, di-fucosyl branches, namely Fuc2, 4Sα(1→3)Fuc4S, were also found to be attached to the O-3 of GlcA. The antidiabetic activity of FCS sj was evaluated using glucosamine induced insulin resistant (IR) Hep G2 cells in vitro . It was found that FCS sj significantly promoted the glucose uptake and glucose consumption of IR-Hep G2 cells in a dose-dependent manner, and could alleviate the cell damage. Furthermore, FCS sj could promote the glycogen synthesis in the glucosamine-induced IR-Hep G2 cells. These results provided a supplement for studying the antidiabetic activity of FCS sj .